VERTICAL INTEGRATION IN FOOD INDUSTRY - Daruka, Peeyush (2012)
Vertical integration has become an important business strategy to respond to the needs of a consumer-driven marketing system. Although one of the perceived benefits of vertical ownership integration is improved profitability of the integrated firm, empirical literature mostly ignores this issue. Using a sample of a leading food and support services players – Compass Group Plc. this study examines the feasibility of vertical mergers on behalf of the firm.